(untitled) (Global Journal of Medical Research, 2016)
Endometriosis, a disease of unknown etiology, remains a cause of significant morbidity in reproductive age women resulting in chronic pelvic pain. Several mechanisms could explain the relationship between endometriosis and pelvic pain, and are potential targets of therapies. Endometriosis-associated pain can be treated with medical therapies or surgery, both conservative and radical. The medical therapies induce a hormonal steady state that results in an environment not conducive for endometriosis development. Surgical therapies for endometriosisassociated pain include conservative treatments such as removal of endometriotic implants, nodules, and adhesions with restoration of normal pelvic anatomy. Radical surgery involves removal not only the uterus with or without of the ovaries in patients who have completed childbearing, but also all residual pelvic lesions.